ANTECEDENT KEPERCAYAAN DAN KEPUTUSAN PEMBELIAN - Hayuningtyas, Widiastuti Hapsari; Widiyanto, Ibnu (Faculty of Economics and Business Diponegoro University, 2015)
The fast growing of information technology has influenced our daily life, such as internet. The number of internet users tend to grow. One of the most popular activities on internet is online purchase. The aim of this research is to analyze the influences of convenience and website security, on Zysku Xena’s customer purchase decision using trust as an intervening variable. Research samples are 181 Zysku Xena’s customers who have purchased on Zysku Xena’s website. The results indicate that convenience and website security have positive influence on trust. Convenience, website security, and trust have positive effect on customer purchase decision. In the first regression result, convenience gives the greatest influence on trust. On the second regression result, convenience also gives the greatest influence on customer purchase decision. Sobel test result indicates that trust become mediating variable between convenience on customer purchase decision, and website security on purchase decision.